Faktor-faktor yang Menyebabkan Rendahnya Kontrol Diri Siswa - Monica, Adella; Suhaili, Neviyarni (Lembaga Yasin AlSys, 2024)
This research is motivated by the phenomenon where students cannot control themselves, such as getting into fights because of their lack of self-control, skipping classes, smoking because their friends do too and following the negative things their friends do. This research aims to describe the factors that cause students' low self-control and ensure that they receive guidance and counseling services. This type of research uses a quantitative approach with descriptive methods. The population of this study was 667 students of SMA N 1 Ampek Angkek who were registered in the 2023/2024 academic year, the research sample was 158 students. Sample selection used purposive sampling technique. The data collection technique uses a self-control scale. Data were analyzed using descriptive techniques. The research results show that the factors that cause students' overall low self-control are in the high category. Based on the indicators, the cause is age factor at 51%, cognitive factor at 55%, cultural factor at 42%, situation at 46% in the medium category. The cause of personality factors is 43%, experience is 35%, family environment is 43% in the high category. The cause of the role of parents is 34% in the very high category. Guidance and counseling services are provided to students whose factors causing low self-control are in the high and very high categories, namely personality factors, experience, family environment and the role of parents. Services can be provided by guidance and counseling teachers to reduce the factors that cause students' low self-control through information services, content mastery services, group guidance services and individual counseling to increase students' self-control.